THE POSSIBILITY OF SENSE-DATA AND ITS TRUTH VALUE IN EARLY KALÓM LITERATURE - ABDUL BASIT ZAFAR (Hamdard Islamicus, 2021)
Though there were plenty of debates on the valid source of knowledge; Is it reason or sense-data? Until Plato, apart from Sophist, no one doubted the possibility of knowledge. Along with Sophists, the debate took a new turn. The questions they asked were doubting the validity of acquired knowledge and the possibility of any knowledge at all. So, is there a possibility of attaining true knowledge about anything? In Islamic thought, such a problem of epistemology was first entertained by Mu‘tazilite theologians. It could be said that one of the terms that formed the epistemological understanding of classic theologians and consequently shaped the form of classic Islamic thought is senses (×is, ×avÉs). The subject of this study is to analyze the various motives laying under their epistemological attitude. The present study is aimed to give a brief view of theological speculation on sense-data, how it came to be accepted as certain and became dogmatic truth for attaining true knowledge. It is argued that in the early period of theological formation, apart from sam‘iyyÉt (valid news) and ‘aqliyÉt (sound reasoning), ÍissiyÉt (senses) were considered an integral part of the epistemological triad. It can be seen that Islamic theology build its foundations on reason and revelation, for both sense-data plays an important role. If senses in themselves or the data collected by these senses are not valid enough, on what grounds then early KalÉm creed establish its truth value. Afterwards, the study aims to question the reliability of the senses from a theological perspective.